Coupling Effect of Water and Proteoglycans on the In Situ Toughness of Bone. (2nd February 2016) - Wang, Xiaodu; Xu, Haoran; Huang, Yehong; Gu, Sumin; Jiang, Jean X
ABSTRACT: Proteoglycans (PGs) are one type of noncollagenous proteins in the extracellular matrix of bone that primarily contain a core protein and glycosaminoglycans (GAGs). GAGs are highly polar and negatively charged, thus have a strong tendency to attract water molecules into the matrix. We hypothesized in this study that PGs in bone play a pivotal role in sustaining the toughness of the tissue only when water is present. To test the hypothesis, we used a novel nanoscratch test to measure the in situ toughness of human cadaveric bone treated with and without peptide‐N‐glycosidase F (PNGase F), an enzyme that specifically removes the N‐linked oligosaccharides of GAGs from core proteins. Cortical bone specimens were prepared from the posterior aspect of mid‐diaphyseal femurs of six ( n = 6) male human donors between 51.5 ± 5.17 years old. Biochemical and histochemical assays were used to verify whether N‐linked oligosaccharides were removed from bone matrix by PNGase F. By testing wet and dehydrated bone specimens, the coupling effect between water and PGs on the in situ toughness of bone was investigated. The two‐way ANOVA analyses showed that removal of GAGs had significant effects on the in situ toughness of wet bone samples. In contrast, the removal of GAGs did not show significant effects on the toughness of dry bone. The results of this study, for the first time, suggest that GAGs play a pivotal role in the in situ toughness of bone only when water is present, and vice versa, water functions as a plasticizer in bone only when GAGs are present. © 2015 American Society for Bone and Mineral Research.